CRAT downregulation promotes ovarian cancer progression by facilitating mitochondrial metabolism through decreasing the acetylation of PGC-1α - Zhen Zhang; Shuhua Zhao; Xiaohui Lv; Yan Gao; Qian Guo; Yanjie Ren; Yuanyuan He; Yihua Jin; Hong Yang; Shujuan Liu; Xiaohong Zhang (Cell Death Discovery)
Abstract Mitochondrial dysfunctions are closely associated with different types of disease, including cancer. Carnitine acetyltransferase (CRAT) is a mitochondrial-localized enzyme catalyzing the reversible transfer of acyl groups from an acyl-CoA thioester to carnitine and regulates the ratio of acyl-CoA/CoA. Our bioinformatics analysis using public database revealed a significant decrease of CRAT expression in ovarian cancer (OC). However, the functions of CRAT have rarely been investigated in human cancers, especially in OC. Here, we found a frequent down-regulation of CRAT in OC, which is mainly caused by up-regulation of miR-132-5p. Downregulation of CRAT was significantly associated with shorter survival time for patients with OC. Forced expression of CRAT suppressed OC growth and metastasis by inducing cell cycle arrest and epithelial to mesenchymal transition (EMT). By contrast, CRAT knockdown promoted OC growth and metastasis. Mechanistically, we found that CRAT downregulation promoted OC growth and metastasis by increasing mitochondrial biogenesis to facilitate mitochondrial metabolism through reducing the acetylation of peroxisome proliferator-activated receptor-γ coactivator (PGC-1α). In summary, CRAT functions as a critical tumor suppressor in OC progression by enhancing PGC-1α-mediated mitochondrial biogenesis and metabolism, suggesting CRAT as a potential therapeutic target in treatment of OC.